Membangun Hubungan Industrial Yang Responsif Dan Berkeadilan Di Era Revolusi Industri 4.0 Pada PT. Sumber Alfaria Trijaya Tbk - Resya Dwi Marselina; Nugraha Rhamdani; Iis Nurkamilah; Septiani Septiani; Ibda Nisaul Wahdah; Miftahul Fadillah (STIKes Ibnu Sina Ajibarang, 2024)
In the era of Industry 4.0, profound changes are reshaping the industrial landscape, significantly influencing industrial relations. This research aims to investigate the strategies and practices necessary for establishing responsive and fair industrial relations. Through a descriptive analysis approach, this study identifies a new framework that integrates advanced technology with inclusive human resource management practices. The results highlight the necessity of close collaboration among industry stakeholders, government, and educational institutions to adapt to technological changes and support the development of an adaptive workforce. In conclusion, building responsive and fair industrial relations requires a holistic transformation in organizational culture and active engagement from various stakeholders to achieve equality and resilience in the Industry 4.0 era.